Persepsi Masyarakat terhadap Perilaku Merokok Saat Berkendara sebagai Potensi Pelanggaran Lalu Lintas - Vania Andari Damanik; Zikra Askalani Azis; Nurliman Prasetyo; Sukri Padil Dongoran (Kampus Akademik Publiser, 2026)
Smoking while driving is a phenomenon that is still frequently encountered on public roads. This behavior not only has the potential to disrupt the driver's concentration but may also endanger the safety of other road users. In the perspective of traffic safety, drivers are required to maintain full concentration and comply with applicable traffic regulations. Therefore, smoking while driving deserves attention as a behavior that potentially leads to traffic violations. This study aims to determine public perceptions of smoking while driving and to examine how society views the potential traffic violations arising from such behavior. The research employs an empirical legal research method with a descriptive approach. The data were collected through the distribution of questionnaires to several respondents in order to understand their views regarding smoking while driving on public roads. The collected data were then analyzed descriptively to illustrate public perceptions of the phenomenon. The results of the study indicate that most respondents believe that smoking while driving can interfere with the driver’s concentration and potentially endanger other road users. In addition, the majority of respondents also agree that such behavior should receive greater attention in efforts to improve traffic safety. Therefore, smoking while driving can be regarded as a behavior that potentially creates safety risks and requires attention in the enforcement of traffic discipline.